GAMBARAN NOMOPHOBIA PADA REMAJA (Jurnal Keperawatan Indonesia Florence Nightingale, 2021)
ABSTRACT The results of a survey conducted by the Indonesian Internet Service Providers Association (APJII) in 2018 said that 90% of internet users were aged 15-19 years and 80% of them were junior high school students. The high use of smartphones among teenagers can cause physical and psychological health problems, one of which is nomophobia. Nomophobia is anxiety caused by no contact or access to his cellphone. This study aims to determine the description of nomophobia in adolescents at SMPN 1 Dayeuhkolot. Descriptive research design with a population of 1363 students. Sampling using propotional random sampling technique of 310 students. The questionnaire used was Nomophobia Questionnare (NMP-Q) which was modified and had been tested for validity. Statistical tests use univariate analysis. Data collection is done online using google form. The results showed that 132 students (42.6%) had mild nomophobia, 45 students (14.5%) had moderate nomophobia and 133 students (42.9%) had severe nomophobia. Conclusion nearly half of the teenagers at SMPN I Dayeuhkolot experienced severe nomophobia. It is recommended that health education interventions be given about the effects of nomophopia, diverting the use of smartphones for learning activities. ABSTRAK Hasil Survey yang dilakukan oleh Asosiasi Penyelenggara Jasa Internet Indonesia (APJII) tahun 2018 mengatakan bahwa 90% pengguna internet adalah usia 15-19 tahun dan 80% penggunaanya yaitu pelajar SMP. Tingginya penggunaan smartphone dikalangan remaja dapat menyebabkan masalah kesehatan fisik maupun kejiwaan salah satunya adalah nomophobia. Nomophobia merupakan kecemasan yang terjadi akibat tidak ada kontak atau akses terhadap ponselnya. Penelitian ini bertujuan untuk mengetahui gambaran nomophobia pada remaja di SMPN 1 Dayeuhkolot. Desain penelitian deskriptif dengan populasi sebanyak 1363 siswa. Pengambilan sampel menggunakan teknik propotional random sampling sebanyak 310 siswa. Kuisioner yang digunakan yaitu nomophobia Questionnare (NMP-Q) yang dimodifikasi dan telah dilakukan uji validitas. Uji statistik menggunakan analisa univariat. Pengumpulan data dilakukan secara online menggunakan google form. Hasil penelitian menunjukkan bahwa 132 siswa (42.6%) mengalami nomophobia ringan, 45 siswa (14.5%) mengalami nomophobia sedang dan 133 siswa (42.9%) mengalami nomophobia berat. Kesimpulan hampir setengahnya remaja di SMPN I Dayeuhkolot mengalami nomophobia berat. Disarankan agar diberikan intevensi pendidikan kesehatan tentang dampak nomophopia, mengalihkan penggunaan smartphone untuk kegiatan pembelajaran.